Syntactic Grammatical Interference in English Communication among Madurese EFL Students: Forms and Contributing Factors - Nuriyah Sa'adah; Mirjam Anugerahwati; Nurenzia Yannuar (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
Grammatical interference is defined as the influence of a first language on the use of a second language, resulting in deviations from the target language's grammatical rules. This phenomenon is commonly observed among foreign language learners, such as students at an Islamic boarding school in Probolinggo, East Java, who use English for daily communication. These students frequently transfer grammatical structures from Madurese, their first language, into English, which leads to various forms of interference. The present study seeks to identify the forms of grammatical interference in English communication and to analyse the contributing factors. A descriptive qualitative approach was adopted. Data collection involved conversation tests based on predetermined themes and interviews to investigate the causes of grammatical interference. The findings reveal that students' grammatical interference primarily manifests as syntactic interference, which can be categorised into three types: predication structure, active-interrogative sentences, and negative-interrogative sentences.  fossilisation of English language usage. These results support the language interference theory proposed by Weinreich (1953) and suggest that English language instructors should develop more effective teaching strategies to minimise grammatical interference and improve students' English proficiency.